2008
DOI: 10.1111/j.1365-2672.2007.03722.x
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of high pressure and nisin on germination and inactivation ofBacillusspores in milk

Abstract: Summary Aims:  The aim of this work was to investigate the germination and inactivation of spores of Bacillus species in buffer and milk subjected to high pressure (HP) and nisin. Methods and Results:  Spores of Bacillus subtilis and Bacillus cereus suspended in milk or buffer were treated at 100 or 500 MPa at 40°C with or without 500 IU ml−1 of nisin. Treatment at 500 MPa resulted in high levels of germination (4 log units) of B. subtilis spores in both milk and buffer; this increased to >6 logs by applying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…First, spores are induced by high pressure to rapidly release Ca-DPA, and the partly hydrated spores are subsequently killed by the combination of pressure and heat due to their increased overall stress sensitivity (Margosch et al, 2004;Reineke et al, 2011). Most of existing mechanistic studies have also reported that the release of dipicolinic acid is accompanied by a loss of heat resistance of endospores during PATP (Black et al, 2008;Paidhungat et al, 2002). In our study, PATP with 3 min treatment resulted in a significant (P < 0.05) heat sensitive spore population among the survivors of B. amyloliquefaciens spores suspended in beef broth (Fig.…”
Section: Heat Sensitivity Of Patp/hpp Treated B Amyloliquefaciens Spmentioning
confidence: 96%
“…First, spores are induced by high pressure to rapidly release Ca-DPA, and the partly hydrated spores are subsequently killed by the combination of pressure and heat due to their increased overall stress sensitivity (Margosch et al, 2004;Reineke et al, 2011). Most of existing mechanistic studies have also reported that the release of dipicolinic acid is accompanied by a loss of heat resistance of endospores during PATP (Black et al, 2008;Paidhungat et al, 2002). In our study, PATP with 3 min treatment resulted in a significant (P < 0.05) heat sensitive spore population among the survivors of B. amyloliquefaciens spores suspended in beef broth (Fig.…”
Section: Heat Sensitivity Of Patp/hpp Treated B Amyloliquefaciens Spmentioning
confidence: 96%
“…To increase the efficiency of HHP against pathogens including spores, some research works focus on its combination with other parameters, such as: the addition of antibacterial compounds such as nisin, xanthenes derivatives (Roberts and Hoover 1996; Gao and Ju 2007b; Black et al. 2008; Zhang and Mittal 2008) or the use of irradiation (Crawford et al.…”
Section: The Development Of Hhp Food Processesmentioning
confidence: 99%
“…To solve this problem, the combination of HHP with other hurdle technologies (Leistner, 2000) has been investigated. One of these combinations with an interesting potential is the use of natural antimicrobials, such as nisin and=or sucrose laureate, which have been applied in some dairy products (Roberts and Hoover, 1996;Stewart et al, 2000;Black et al, 2008), to inactivate spores of B. cereus, Bacillus coagulans, B. subtilis, and Clostridium sporogenes. The inactivation of B. cereus spores has also been achieved by HHP combined with moderated temperatures (Raso et al, 1998;Ju et al, 2008).…”
Section: Introductionmentioning
confidence: 99%